Chinese labour in South Africa, 1902-10 : race, violence, and global spectacle - Bright, Rachel, 1979- (Cambridge imperial and post-colonial series., 2013)
"At the beginning of the twentieth century, 'white' colonies around the world had restricted Asian migration, associated with immorality, disease, and a threat to 'white' labour. The 'Yellow Peril' was in full swing. And yet, in 1904, the British government imported over 64,000 Chinese indentured labourers to work on gold mines in Southern Africa. This book explores the decision to import Chinese labour so soon after the empire had fought to secure Southern Africa for the British Empire and despite the already tense racial situation in the region. This enables a clearer understanding of racial and political developments in Southern Africa during the reconstruction period and the formation of South Africa the nation. It places these localised issues within a wider historiography, such as research into colonial violence, moral panics and Black Perils, networks of labourism and whiteness, and economic imperialism. Through this book one can trace the complicated negotiations between national and imperial identities, between independence and patriotism, and giving a clearer sense of how trans-colonial relationships evolved"--